ASSESSING THE ROLE OF COAGULATION ASSAYS IN THE MANAGEMENT OF BLEEDING DISORDERS: A REVIEW OF LABORATORY TECHNIQUES AND CLINICAL IMPLICATIONS - Turky Ahmed Althobaiti; Abdulrahman Mohammed Al Suyan; Abdulrahman Abdulqader Alshamrani; Maram Abdullshaheed Alabadi; Ahmed Faya Asiri; Abdullah Mari Alqarni; Mohammed Abdualrhman Alghamdi; Younis Ibrahem Assiri; Yousef Abdulaziz Meqbil Althobaiti; Mustafa Hussain Alameer; Naif Enad Alanazi (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Coagulation assays are critical tools in the management of bleeding disorders, offering insights into the complex mechanisms of hemostasis and informing clinical decisions. Bleeding disorders present diverse challenges due to their varied pathophysiological bases, necessitating precise diagnostic and management strategies. Traditional assays such as Prothrombin Time (PT) and Activated Partial Thromboplastin Time (aPTT) provide foundational data on the extrinsic and intrinsic pathways of the coagulation cascade but often lack the sensitivity to detect mild deficiencies or to accurately predict bleeding risks in non-hemophilic disorders. Recent advancements have introduced more sophisticated techniques like thromboelastography and chromogenic assays, which deliver a dynamic and comprehensive view of the clotting process. These advanced methods not only improve diagnostic accuracy but also offer timely data crucial for managing acute cases and surgical interventions. However, the adoption of such technologies in everyday clinical practice is hindered by high costs, the need for specialized equipment, and complex interpretation of results. The integration of coagulation tests with detailed clinical evaluations is essential to customize treatment plans effectively, acknowledging the substantial variability in test results due to individual patient factors and external influences. This variability highlights the challenges in interpreting coagulation assays and underscores the necessity of a cautious approach that combines laboratory data with clinical insights. Future developments in coagulation testing are expected to lean towards a hybrid model that leverages both traditional and modern techniques. Ongoing research and clinical validation are crucial to refining these methods, ensuring that coagulation assays continue to evolve as reliable, efficient tools in the management of bleeding disorders, thereby enhancing overall patient care.